2020
DOI: 10.1177/2055102920975274
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy eating and academic stress: The moderating effect of eating style and BMI

Abstract: This study aimed to evaluate the relationship between stress and unhealthy eating among undergraduate students, considering the moderation effects of BMI, eating style, and nationality. A total of 748 Italian and French students completed self-report measures of academic stress, emotional eating, restrained eating, BMI, and unhealthy eating intake. Results showed that academic stress increased unhealthy food consumption in Italian students, whereas it reduced junk food consumption in French students. Negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 77 publications
3
14
0
3
Order By: Relevance
“…We also found that a higher frequency of stressed eating and overeating in college students was significantly correlated with a higher stress level. Parallel to this finding, previous studies (Caso et al 2020;Kaplan and Kaplan 1957;Penaforte et al 2016) showed that college students used food as a dysfunctional coping strategy to reduce stress. As a result, they tend to eat more when they feel stressed.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…We also found that a higher frequency of stressed eating and overeating in college students was significantly correlated with a higher stress level. Parallel to this finding, previous studies (Caso et al 2020;Kaplan and Kaplan 1957;Penaforte et al 2016) showed that college students used food as a dysfunctional coping strategy to reduce stress. As a result, they tend to eat more when they feel stressed.…”
Section: Discussionsupporting
confidence: 54%
“…Increased academic stressors and stress levels in college students can impact health-related behaviours, such as eating (Caso et al 2020). Several previous studies have shown that high levels of stress in college students are associated with increases in unhealthy food consumption, especially snacks and fast food (Errisuriz et al 2016;Liu et al 2007;Mikolajczyk et al 2009;Penaforte et al 2016;Zellner et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of knowledge about the disease, the sudden and unexpected nature of the pandemic, the fear of contracting the virus, the social isolation and the constant media bombardment about the spread of the virus could have caused high levels of psychological distress ( Arslan et al, 2020 , Capone et al, 2020 , Di Renzo et al, 2020 , Wang et al, 2020 ). It has been widely confirmed that stress and negative emotional states can affect eating behaviour, altering both the amount of food consumed (increasing or reducing it) and the choice of food ( Caso et al, 2020 , Hill et al, 2018 , Reichenberger et al, 2018 , Torres and Nowson, 2007 ). More specifically, negative emotions, in particular anxiety and fear, can result in excessive food consumption and a tendency to consume unhealthy foods (e.g., high-fat snack foods) as a strategy to avoid or reduce such negative emotions ( Macht, 2008 , Wallis and Hetherington, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…For young adults, the college years present many challenges to the maintenance or development of healthy behaviors (e.g., regular physical activity, high quality diets) [ 1 , 2 , 3 , 4 ]. Of particular concern are college women, who face barriers such as lack of knowledge, misinformation, poor body image, social pressures, and time obligations that may cause strain on their motivation and self-efficacy for appropriate and healthy engagement in physical activity and dietary habits [ 3 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%